(3SeGY deSfO CMeO Ydi Hf GdLRQis - (3CMeO Ydj GdLRQjs
(3ChdgG (B:s
(3CeG HYO abO SeY GdfUa GdChd ef eSfO GdEeGe GdCYXe CHj YHO Gddg CMeO Hf eMeO Hf MfHd Hf gdGd Hf GSO GdTjHGfi QMeI Gddg hgh CQHYI CLRGA gPG BNQgG Ydi GdTjN eMeO Hf eMeO Hf eMeO GdLRQi s
(3BNQgG (B:s
(3eSfO LGjQ Hfg YHO Gddg eSfO CHj gQjQI eSfO GdYHGS hHfjg eSfO YGFTI QVi Gddg YfgG hQVi Yfge CLejYf hMSHfG Gddg hfYe Gd hcjd s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdYHOdjI GdUGObjI (B/ (3JhfS (B(1687) s
Keywords: (3GdMOjK h GdeUWdMs